2021
DOI: 10.1152/ajpgi.00415.2020
|View full text |Cite
|
Sign up to set email alerts
|

Targeted intestinal deletion of Rho guanine nucleotide exchange factor 7, βPIX, impairs enterocyte proliferation, villus maturation, and mucosal defenses in mice

Abstract: Rho guanine nucleotide exchange factors (RhoGEFs) regulate Rho GTPase activity and cytoskeletal and cell adhesion dynamics. βPix, a CDC42/RAC family RhoGEF encoded by ARHGEF7, is reported to modulate human colon cancer cell proliferation and post-wounding restitution of rat intestinal epithelial monolayers. We hypothesized βPix plays a role in maintaining intestinal epithelial homeostasis. To test this hypothesis, we examined βPix distribution in the human and murine intestine and created mice with intestinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…Supporting the functional importance of MR agonist-induced βPix binding to β-catenin, we found that reducing βPix expression in vitro attenuated M 3 R agonist-induced colon cancer cell proliferation, migration, and invasion. Moreover, in the AOM/DSS murine model of colon cancer, mice with conditional intestinal epithelial cell βPix deficiency 59 had significantly fewer colon tumors, primarily fewer adenocarcinomas, a finding exaggerated in animals treated with a MR agonist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supporting the functional importance of MR agonist-induced βPix binding to β-catenin, we found that reducing βPix expression in vitro attenuated M 3 R agonist-induced colon cancer cell proliferation, migration, and invasion. Moreover, in the AOM/DSS murine model of colon cancer, mice with conditional intestinal epithelial cell βPix deficiency 59 had significantly fewer colon tumors, primarily fewer adenocarcinomas, a finding exaggerated in animals treated with a MR agonist.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting the M 3 R/βPix/β-catenin axis has therapeutic potential. Our experience using Arhgef7 CKO mice with intestinal epithelial cell-selective βPix deficiency suggests targeting intestinal βPix would be safe; Arhgef7 CKO mice are healthy and fertile with modest phenotypic changes 59 . Lastly, since other upstream receptors act through PKC-α, our findings may be mechanistically relevant to other receptors and signaling pathways in colon neoplasia and other cancers in which muscarinic receptor signaling plays a prominent role.…”
Section: Discussionmentioning
confidence: 99%
“…4) and can induce membrane ruffling, it is also involved in cell migration, attachment and spreading. In particular, ARGHEF7 function was associated with intestinal cell maturation and proliferation in mice [51]. According to the study, ARHGEF7 is essential for normal small intestinal epithelial cell proliferation, villus development and mucosal resistance to injury.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, ARGHEF7 function was associated with intestinal cell maturation and proliferation in mice [51].…”
Section: Arhgef7mentioning
confidence: 98%
“…Herein, evolutionary forces acting on cytoskeletal organization-related genes (ARHGEF7 and CADM2) provided additional evidence reflective of thermal selection in O. oratoria. ARHGEF7 can regulate Rho GTPase activity and plays a role in regulating cytoskeletal and cell adhesion dynamics (Cheng et al, 2021), while CADM2 is a cell adhesion molecule that functions in cell recognition, adhesion, migration and differentiation (Edelman, 1983). Selection on genes involved in cytoskeletal organization has also been implicated in the warm-adapted marine mussel Mytilus galloprovincialis compared with its cold-adapted congeners (Popovic and Riginos, 2020).…”
Section: Environmental Heterogeneity Driving Adaptive Divergence In O...mentioning
confidence: 99%